Task-Based Language Teaching: A Systematic Review of Research and Applications - Adam Mudinillah; Sri Nur Rahmi; Nanakorn Taro (Lingeduca: Journal of Language and Education Studies, 2024)
Task-Based Language Teaching (TBLT) has gained widespread recognition as an effective approach in language education, emphasizing meaningful communication and real-world language use. TBLT focuses on learners completing tasks that mirror authentic language use, promoting both linguistic and communicative competence. Despite its popularity, challenges in implementation, teacher training, and resource availability have raised questions about its effectiveness across different educational contexts. This systematic review aims to evaluate the research and applications of TBLT, analyzing its impact on language proficiency, student engagement, and instructional outcomes. The review includes qualitative and quantitative studies from various contexts, ranging from primary to higher education, as well as English as a Foreign Language (EFL) and English as a Second Language (ESL) settings. The findings reveal that TBLT enhances language acquisition, particularly in developing speaking and listening skills, and fosters greater learner autonomy. However, successful implementation requires adequate teacher training and institutional support. Challenges such as curriculum alignment and assessment remain significant obstacles in some educational environments. Despite these issues, TBLT consistently promotes higher levels of student engagement and motivation. In conclusion, TBLT offers considerable benefits for language learning, but its success is highly dependent on contextual factors such as teacher preparedness and curriculum flexibility. Further research is needed to explore long-term outcomes and effective strategies for overcoming implementation barriers.